FACTORS ASSOCIATED WITH WORK STRESS IN HEALTH PROFESSIONALS BEFORE AND DURING THE COVID-19 PANDEMIC IN THE HOSPITAL CONTEXT: IMPACTS OF SOCIODEMOGRAPHIC, CLINICAL AND OCCUPATIONAL CONDITIONS - Andrade Barbosa, Henrique; Ferreira da Silva Junior, Rene; Teixeira Andrade, Túlio; Danyella Alves Leão Ribeiro, Claudia; Cristina Santos Alves Souto, Elaine; D`Paula Ribeiro Vieira Torres, Jaqueline; Paiva Santos Rocha, Silvânia; de Pinho, Sirlaine; Gonçalves Silva Pereira, Sabrina; Silvana de Oliveira e Silva, Carla (Revista Gênero e Interdisciplinaridade, 2026)
Objective: to investigate the factors associated with work-related stress in healthcare professionals in the hospital setting, before and during the COVID-19 pandemic. Methods: An integrative literature review was conducted based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRIS) guidelines. The search for scientific publications took place from January to March 2023, and was conducted through consultation of PubMed, BVS, Cochrane, and Science. The search terms used are registered in Medical Subject Headings (MeSH), namely: “Stress” (in French), “Occupational Stress”, “Health Personnel”, “Hospitals”. Cross-sectional and longitudinal studies with a quantitative approach; clinical trials; quasi-experimental studies; and cohort studies that assessed work-related stress in hospital professionals were included. The methodological quality of the studies was assessed using the GRADE system. Results: The sample for this review consisted of fifteen studies. According to databases, they are distributed as follows: eight (8) indexed in BVS, six (6) PubMed and one (1) from Science. Regarding research design: 14 (93.3%) studies are cross-sectional and 1 (6.7%) longitudinal study. Regarding methodological quality, seven (46.7%) studies were classified as high level of evidence; six (40.0%) as moderate and two (13.3%) defined as low level. Final considerations: Occupational stress before the pandemic was associated with labor issues, service organization, unit of operation, professional category, experiences and demographic, social and psycho-emotional factors. On the other hand, work stress in the pandemic situation was linked to the fear of contamination from direct contact with patients infected by SARS-CoV-2, the insufficiency of PPE, the overwhelming demand of patients, the absence of a vaccine and specific treatment against the disease.